TOLERANCE OF FRESHWATER BIVALVE Cyanocyclas brasiliana (Deshayes, 1854) TO THE VARIATION OF SALINITY IN LABORATORY CONDITIONS: Tolerância do bivalve dulcícola Cyanocyclas brasiliana (Deshayes, 1854) à variação de salinidade em condições de laboratório - Suzy Freire de Brito, Carla; Gomes de Sousa, Ronaldo; Rial Conde, Diego; Rocha-Barreira, Cristina de Almeida (Arquivos de Ciências do Mar, 2022)
The species Cyanocyclas brasiliana (Deshayes, 1854) is endemic to South America and occurs in northern Brazil, in the state of Amazonas, Pará and Piauí. The present study was carried out in the Parnaíba River estuary, Piauí, Brazil. The objective of this study was to verify the tolerance limit and survival of the freshwater bivalve Cyanocyclas brasiliana submitted to an increasing salinity gradient under laboratory conditions. The specimens (19.49 to 26.47 mm) were kept in containers with 2 liters of water with constant aeration and at a density of 2.5 animals per liter. 7 treatments (salinities of 0, 1, 2, 3, 4, 5 and 6) were performed with 5 replicates per treatment. In the first 36 hours there was no death of any individual; mortality started after 48 hours at 3, 4, 5 and 6‰; it was more significant from 72 to 96 hours for treatments ranging from 2 to 6‰ and every specimen for treatments of 2 and 3‰ died from 120 to 144 hours. LC50 ranges from 3.1 at 72 h and 3.3 at 84 h, so the limiting average salinity was 3.2‰ and this species is characterized as stenohaline. Lethal death time (LT50) was: 81.8, 82.3, 78.5, 61.1 and 63.5 h for salinities of 2, 3, 4, 5 and 6‰ respectively. This species does not support great variations in salinity under experimental conditions, being well adapted to survive in salinities between 0 and 1. Keywords: endemic, mortality, survival